After Discovery - Evert Gummesson; Hans O. Thulesius; Alvita Nathaniel; Tom Andrews; Antoinette M. McCallin; Mark S. Rosenbaum; Astrid Gynnild; Walter D Fernández (Grounded Theory Review: An International Journal)
Grounded Theory 40 Years - A Jubilee Extraordinaire. Evert Gummesson, Ph.D.